A Review of India's Para-Teachers (International Journal of Innovative Research in Engineering & Management, 2023)
This article gives an overview of India's  'para' instructors. It recounts the beginnings of para-teacher  programs in the nation and examines the shifting policy  environment in which contract para teachers with little pay  and training are increasingly being hired in lieu of regular  teachers. Teachers at public schools. Incorporating  existing research. The authors of the research call attention  to the negative consequences that the purpose of para teacher programs is to help teachers become more  professional. Concerns about educational quality and  equality. Another significant development in the past  decade is Parliament's adoption of a Constitutional  Amendment making education for children aged 6 to 14  years a basic right of all citizens. . Meanwhile, via the  National Literacy Mission, efforts to improve literacy were  galvanized with mass literacy campaigns across the length  and width of the nation. Another significant development  in the past decade is Parliament's adoption of a  Constitutional Amendment making education for children  aged 6 to 14 years a basic right of all citizens. The process  of drafting central legislation to make the constitutional  clause effective is now ongoing
Keywords: Constitutional Amendment; Education in India; Para Teachers; Para Instructors; Quality of Education; Regular Teachers